Non-instrumental clinical monitoring does not guarantee an adequate course of general anesthesia. A prospective clinical study - Szostakiewicz, Katarzyna; Rybicki, Zbigniew; Tomaszewski, Dariusz (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc, Czechoslovakia, 2018)
Clinical monitoring is the most common method of adjusting the appropriate level of general anesthesia. However, episodes of intraoperative awareness (AWR) are still reported, suggesting that clinical observations may not be sufficient in some cases. The objective of this study was to compare the efficacy of clinical and instrumental neuromonitoring with auditory evoked potentials (AEP) in an intraoperative analysis of the proper level of general anesthesia. Patients scheduled for elective surgery were randomly divided into two groups. Subjects in the first group underwent intravenous, in the second group volatile anesthesia. The adequacy of anesthesia was analyzed using clinical parameters. All the participants were instrumentally monitored with the autoregressive AEP index (AAI). After the anesthesia, patients filled out a questionnaire on possible AWR. Data of 208 patients (87 in the first, and 121 in the second group) were analyzed. Before surgery there were no changes in AAI values between groups (80 vs. 78, P=0.5192). The mean values of clinical parameters changed, but five minutes after the nociceptive stimuli. The mean values of AAI at analyzed time points were specific for general anesthesia. In patients under intravenous anesthesia, we found more episodes of too low (46/608 vs.15/847, P<0.000) anesthesia. One case of AWR was found in the TIVA group. AAI index is good indicator of patients' level of consciousness during general anesthesia. Standard clinical monitoring provides appropriate level of the procedure. However, it is insufficient during TIVA and does not prevent episodes of AWR.